Can Institutional Trust Strengthen Gold Investment Intention? Evidence from the Interplay of FoMO, Financial Literacy, and Long-Term Investment Motivation - Siti Aminatus Zuhro; Noor Shodiq Askandar; Harun Alrasyid (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study aims to analyze the influence of Fear of Missing Out (FoMO), financial literacy, and long-term investment motivation on gold investment intention, and to examine the moderating role of institutional trust.Method: This study employed a quantitative causal explanatory design targeting individuals interested in gold investment. Respondents were selected based on specific criteria: being at least 17 years old, having prior knowledge of gold investment, and showing interest in using gold investment products. Data were collected through structured questionnaires from 216 eligible respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct and moderating effects among variables.Result: The findings indicate that FoMO, financial literacy, and long-term investment motivation positively and significantly affect gold investment intention. Moreover, institutional trust strengthens the relationships between FoMO, financial literacy, and long-term investment motivation and gold investment intention.Practical Implications for Economic Growth and Development: The results suggest that improving financial literacy, strengthening public trust in Islamic financial institutions, and enhancing the usability and transparency of digital gold investment platforms may encourage stronger public intention to invest in gold. These findings provide practical guidance for Islamic financial institutions and platform providers in designing more accessible, credible, and user-oriented investment services.Originality/Value: This study adds trust to Islamic financial institutions (institutional trust) as the moderator in the context of gold investment intention.